The Relationship between Perception, Interest and Motivation on Women's Participation in Football in the City of Semarang - Wykan Andreawan; Setya Rahayu; Heny Setyawati (Universitas Negeri Semarang, 2024)
The involvement of women in the sport of football has many pros and cons. Psychological studies such as perception, interest and motivation will have an impact on women's involvement or participation in the sport of football. The aim of this research is to determine the relationship between perception, interest and motivation towards women's participation in football in the city of Semarang. The approach used in this research is a quantitative approach with a correlational research type. The population in this study was 100 female soccer players in Semarang City women's soccer clubs, a sample of 100 players with a sampling technique, namely total sampling. Data analysis techniques use simple correlation and multiple correlation. The results of this study show that there is a sufficient relationship between perceptions of women's participation in football in Semarang City with a contribution of 11.7%. There is a strong relationship between interest in women's participation in football in the city of Semarang with a contribution of 20.7%. There is a strong relationship between motivation and women's participation in football in Semarang City with a contribution of 28.9%. There is a strong relationship between perception and interest in women's participation in football in Semarang City with a contribution of 17.2%. There is a strong relationship between perception and motivation towards women's participation in football in Semarang City, with a contribution of 39.1%. There is a sufficient relationship between interest and motivation towards women's participation in football in Semarang City with a contribution of 47.8%. There is a strong relationship between perception, interest and motivation towards women's participation in football in Semarang City with a contribution of 71.8%. Conclusion: there is a relationship between perception, interest and motivation towards women's participation in football in the city of Semarang